Modelling Of Reactive Distillation For The Production Of Methyl Tert-Butyl Ether (MTBE) Parametric Sensitivity Study On Kinetic Model - Mohamed Zubir, Mohamed Fahim (Universiti Sains Malaysia, 2021)
Modelling of reactive distillation for the production of MTBE has been presented in this thesis. A reactive distillation column modelled by using RADFRAC module in the Aspen Plus V10 software for the production of MTBE. The simulation was done on an equilibrium basis. Prior to running the simulation, all the necessary data were collected. The kinetic data which is the coefficients of the equilibrium equation were collected from the equilibrium equation. The values obtained were 357.094, -1492.77, -77.4002 and 0.507563. These values were entered into the Aspen Plus V10 built-in Keq expression. The simulated model was verified by comparing to the published data. Once it was verified, the simulation was then used to carry out parametric sensitivity study on kinetic model. The effect of changes in the kinetic data and four different operating conditions of choice such as the feed flowrate of methanol, the feed flowrate of mixed butenes, the reflux ratio and the composition of isobutylene on the simulation results in terms of MTBE purity and isobutylene conversion were studied in detail. The individual best values for each operating conditions were determined. Then optimization carried out. The optimized values were 209.3 mol/s for methanol feed flowrate, 583.2 mol/s for mixed butenes feed flowrate, 7 for reflux ratio and 0.357 for isobutylene mole fraction. From these set of values, a MTBE purity and isobutylene conversion of 100.00 % obtained successfully. This study shows that the changes in parameters influences the performance of reactive distillation process for the production of MTBE.